Mathematical modelling and simulatrion of the human arm for control purpose - Mailah, Musa; Md. Zain, Mohd. Zarhamdy; Jahanabadi, Hossein; Abdul Rahim, Mohammad Akmal Baharain (Faculty of Mechanical Engineering, 2009)
The project focuses on the modelling and control of a two-link planar mechanical manipulator that emulates a human arm. The arm is subjected to a vibratory excitation at a specific location on the arm while performing a trajectory tracking tasks in two dimensional space, taking into account the presence of ‘muscle’ elements that are mathematically modelled. A closed-loop control system is applied using an active force control (AFC) strategy to accommodate the disturbances based on a predefined set of loading and operating conditions to observe the system responses. Results of the study imply the effectiveness of the proposed method in compensating the vibration effect to produce robust and accurate tracking performance of the system. The results may serve as a useful tool in aiding the design and development of a tooling device for use in a mechatronic robot arm or even human arm (smart glove) where precise and/or robust performance is a critical factor and of considerable importance. The project is in fact complementing the on-going research in the Faculty of Mechanical Engineering (FME), UTM that is geared towards developing a robust force control system. In addition to that, the research shall also serve as a basis for potential investigation into the field of biomedical related to the application of a robust control technique to effectively control human arm movement particularly when it is subjected to undesirable forcing. The fact that a human arm (to a certain extent) resembles a two-link mechanical linkage serves to provide an analogy leading to the following main and important hypothesis: the control of the human arm’s movement can be effectively carried out using a number of control methods that make use of sensory information just like the mechanical arm counterpart. The results of the study clearly indicate that the modelled arm with ‘muscle’ elements can be simulated to demonstrate the effectiveness and robustness of the control techniques to suppress or reject various disturbances including vibration applied to the system taking into account a number of predefined input trajectories.